Upaya Meningkatkan Perkembangan Motorik Halus Anak melalui Kegiatan Melipat Kertas pada Kelompok B - Sakinah; Yuniatari, Yuniatari (Kiddie: Early Childhood Education and Care Journal, 2024)
The fine motor development of group B children at RA Asy-Syuhada' Pamekasan is still very low. This is caused by the child's lack of interest in the learning methods provided by the teacher. This research aims to improve children's fine motor development through paper folding activities in group B. This type of research is classroom action research which aims to improve the learning process or improve the quality of learning. The research sample consisted of 38 children. Research data is taken through observation, documentation and tests. The research uses the Kemmis and Taggart model which consists of four stages, namely planning, implementation, observation and reflection. The results of the research showed that there was an increase in the development of children's fine motor skills through paper folding activities in group B with the category of children who had developed after doing it for two cycles, namely cycle I and cycle II. In the pre-cycle, children who have developed reach a percentage of 60.5%. In cycle I, children who had developed reached a percentage of 60.5%. In cycle II, children who had developed reached a percentage of 84.2%. The conclusion of this research was that the paper folding activity could improve the fine motor development of children in group B at RA Asy-Syuhada' Pamekasan.